Expression of cell mitotic progression proteins and keratinocyte markers in porcine buccal pouch mucosal cells during short-term, real-time primary culture - Bryja, A; Dyszkiewicz-Konwińska, M; Budna, J; Ciesiółka, S; Kranc, W; Borys, S; Jeseta, M; Urbaniak, O; Bukowska, D; Antosik, P; Bruska, M; Nowicki, M; et al. (Journal of biological regulators and homeostatic agents, 2017)
The porcine model is often used in clinical trials. The pig has many fundamental anatomic, physiological and nutritional similarities to humans. Additionally, the European Medicines Agency (EMA) demands the use large animals in clinical studies. Oral mucosa has received special attention due to its regenerative properties. Oral tissue is composed of several types of cells including fibroblasts and keratinocytes. The porcine oral mucosa/buccal pouch mucosa has a cellular structure with defined proliferation and differentiated capability. In this study, we investigated the expression pattern of porcine buccal pouch mucosal cell proliferation and differentiation markers such as Ki-67, proliferating cell nuclear antigen (PCNA), and involucrin. We observed a clear monolayer culture of spindle-shaped, porcine buccal pouch mucosal cells during 168 h of real-time in vitro culture. The RTCA assays revealed parametric and progressive increases in proliferation after 72 h of IVC. We found an altered proliferation index (PI) in the replicated groups of experiments except through the 144-168 h proliferation period. The RT-qPCR results demonstrated a significant increase in Ki-67 and PCNA expression after 48, 120, and 168 h of IVC as compared to other culture periods (P<0.001). The involucrin mRNA displayed increased expression after 168 h of IVC as compared to other periods. We observed a lack of PCR product at 24 h in the case of Ki-67 and both before IVC (0h) and after 24 h of IVC for PCNA mRNA. When we analyzed the three transcripts together, we found the highest expression of involucrin during each of the culture periods. It has been suggested that Ki-67, PCNA, and involucrin may be successfully used as markers of porcine buccal pouch mucosal cell proliferation and differentiation capability in vitro.
Keywords: Gene Expression Regulation; prasata; Swine; proteiny buněčného cyklu; kultivované buňky; Cells, Cultured; Mitosis; mitóza; keratinocyty; Animals; ústní sliznice; Mouth Mucosa; Cell Cycle Proteins; Keratinocytes; zvířata; regulace genové exprese